Gambaran Status Gizi dan Aktivitas Fisik Anak Usia 6-12 Tahun Di SD Kristen Saumlaki Maluku Tenggara Barat - Mona Susy Mouw; Dary Dary; Dennys Christovel Dese (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: The purpose of this study is to describe the picture of the nutritional status and physical activity of children aged 6-12 yearsMethods: This research method uses descriptive quantitative research methods with a cross sectional approach . This research was conducted at Saumlaki Christian Elementary School, South Tanimbar Subdistrict, West Southeast Maluku Regency in September - October 2021. Sampling technique using probability sampling with the number of respondents 44 boys and girls with the age range of 6-12 years. The data collection in this study used anthropometric measurements to measure nutritional status and IPAQ (International Physical Activity Questionnare) questionnaires to measure physical activity. Results: The results showed the majority of children (81.1%) have undernutrition status and the rest with good nutritional status and more nutrition. Children's physical activity is in the category of moderate physical activity at 51.1%Conclusion: Based on the results of research that has been done, it can be concluded that the nutritional status and physical activity of children aged 6-12 years in Saumlaki Christian Elementary School is quite diverse. This is evidenced by children who have a nutritional status of 81.1%, normal nutritional status 13.6% and nutritional status over 4.5%. Of these percentages, most students in Saumlaki Christian Elementary School have a tendency to undernutrient status. This nutritional status is caused by a lack of energy and protein consumption as well as an irregular diet. Children's nutritional status affects their daily activities.